Content related rights transmission with MPEG-21 in the educational field - Marques, J.; Serrão, C.; Metrolho J. (14th European Conference on e-Learning (ECEL-2015), 2015)
One of the main issues affecting educational content distribution and sharing is to ensure that the terms and conditions defined by the content owners are respected by the others, such as distributors and consumers. Authorship and the content integrity are the most basic rights that authors want to preserve in the educational field. To ensure that content and associated rights are protected, cryptographic techniques and mechanisms are applied to content, rights, protection keys and related metadata that are packaged in a digital object. ARMS is a new platform that was developed to preserve author rights in the educational field applying the MPEG-21 standard concepts. A web based services interface is established with the educational Academic Management System of the Academic institution in order to verify the user eligibility in this domain. After obtaining the usage license the user can send the license to other users, if that privilege has been granted. Our proposal uses MPEG-21 concepts in order to enable rights transmission among the main participants in the educational environment but with a mechanism where the inheritance rights established by the author are uphold. Through the integration between ARMS and the Academic Management Information System hosted in the educational institutions, user academic data can be retrieved in order to verify his eligibility.